The First Genome Survey and De Novo Assembly of the Short Mackerel (Rastrelliger brachysoma) and Indian Mackerel (Rastrelliger kanagurta) - Komwit Surachat; Patcharaporn Narkthewan; Chayanin Thotsagotphairee; Monwadee Wonglapsuwan; Walaiporn Thongpradub (My University, 2022)
Rastrelliger brachysoma (short mackerel) and Rastrelliger kanagurta (Indian mackerel) are commercially important marine species in Southeast Asia. In recent years, numbers of these two species have been decreasing in the wild, and genomic information about them is still limited. We conducted a genome survey of these two mackerel species to acquire essential genomic information using next-generation sequencing data. To obtain this genetic information, comprehensive bioinformatics analyses were performed, including de novo assembly, gene prediction, functional annotation, and phylogenetic analysis. The estimated genome sizes were around 680.14 Mbp (R. brachysoma) and 688.82 Mbp (R. kanagurta). The heterozygosity of these species was very similar (≈0.81), while the repeat content for R. kanagurta (9.30%) was slightly higher than for R. brachysoma (8.30%). Functional annotation indicated that most of the genes predicted in these two species shared very close average amino acid identities (94.06%). The phylogenetic analysis revealed close phylogenetic relationships between these two species and other scombrids. This is the first reported genome survey and assembly of species in the genus Rastrelliger and could be useful for future comparative genomic studies.
Keywords: Genomics and Phylogenetic Studies